Implementasi Strategi Index Card Match Pada Pembelajaran Pkn Kelas V MI Ma'arif NU Banjarsari Banyumas - Darmawan, Aditya; Mayasari, Novi (Jurnal Pendidikan Agama Islam, 2025)
In the teaching and learning process, Strategy is very important to ensure effective and efficient teaching and learning throughout the learning process. Teachers must master various techniques to ensure successful learning. In carrying out learning activities in schools, especially in Civics learning. To achieve these learning objectives, an effective strategy is needed and is in accordance with the material to be delivered, one of which is the Index Card Match strategy. This study aims to describe and describe in depth the Implementation of the Index Card Match Strategy in class V MI Ma'arif NU Banjarsari in Civics learning. This study uses a descriptive qualitative research method, where the focus of this study is more on an in-depth understanding of how the Index Card Match strategy is received, implemented, and interpreted by participants, data collection techniques used Through interviews, observation, and documentation to obtain data and information related to the implementation of the Index Card Match strategy in Civics learning. The results of this study indicate that learning is implemented through the planning, implementation, and evaluation stages. The planning stage includes developing learning modules, studying learning objectives, and preparing teaching materials. The implementation stage includes three activities: preliminary activities, core activities, and closing activities.